EFFECTS OF NATURE OF INDUSTRY, NEGATIVE ECOURAGEMENT AND FLAWED FEGULATRY SYSTEM ON ORGANISATIONAL PERFORMANCE: ROLE OF CORRUPTION IN INDONESIA'S CONSTRUCTION SECTOR - I Putu Gde Indra Yudha; Indrianawati Usman; Nuri Herachwati (Operational Research in Engineering Sciences: Theory and Applications)
The research aims to examine the influence of the nature of the industry, negative encouragement, and a flawed regulatory system on organizational performance through the practice of corruption in the construction industry of Indonesia. To achieve this purpose, cross-sectional self-administered questionnaires were distributed among 350 managers using a convenient sampling technique. The quantitative research approach and Partial Least Squares-Structural Equation Modelling (PLS-SEM) technique were applied for the analysis of the collected data. The results of the regression analysis show that the nature of the industry has a positive and significant impact on organizational performance and the practice of corruption. Similarly, a flawed regulatory framework also has a positive and significant impact on organizational performance and practices of corruption. Negative encouragement also has a positive and significant impact on organizational performance and the practice of corruption. The study reveals that the practice of corruption also has a positive and significant impact on organizational performance. These significant findings contribute to the existing body of literature, providing new insights for future researchers. The research could also assist policymakers and regulators in understanding the importance of these factors to improve organizational performance by addressing corruption practices in the construction industry in Indonesia.